An umbrella review of pharmacist prescribing: stakeholders views and impact on patient outcomes - Eustace-Cook, Jessica; Brady, Anne-Marie; Ryan, Cristn; Cadogan, Cathal (My University, 2024)
Introduction: There is great geographical diversity in the degree of prescribing rights pharmacists have. In some countries such as the United Kingdom (UK), pharmacists have unrestricted prescribing rights following appropriate training; in other countries, pharmacists cannot legally prescribe. The impact of pharmacist prescribing (PP) has been studied in various qualitative and quantitative research studies, but this evidence has not been synthesised to support the development of PP internationally. Aim: The aim of this umbrella review was to describe the international PP models, establish the impact of PP on patient outcomes and describe key stakeholders’ views of PP, by synthesising all the available systematic reviews (SRs). Methods: Six databases (Embase, CINAHL, MEDLINE, Web of Science, Cochrane Library and PsycINFO) were searched, from January 2003 to June 2023, for key terms such as ‘pharmacist’, ‘prescribing’, ‘prescription’ and ‘systematic review’, ‘meta-analysis’, ‘meta-synthesis’
PUBLISHED
Keywords: Pharmacy; Prescribing; Patient; Pharmacy; Prescribing; Patient